1988
DOI: 10.1103/physrevlett.61.1241
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and Resonance Properties of Magnetic X-Ray Scattering in Holmium

Abstract: Be measuring the degree of linear polarization we identify the orbital and spin contributions to the xray magnetic scattering in holmium. When the incident x-ray energy is tuned through the L\\\ absorption edge, we observe a fiftyfold resonant enhancement of the magnetic signal, and resonant integer harmonics. The line shapes of the two linear components scattered parallel and perpendicular to the diffraction plane are distinct in energy with a 6-eV splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
253
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 482 publications
(259 citation statements)
references
References 14 publications
3
253
0
3
Order By: Relevance
“…It has been demonstrated for the first time by Gibbs et al [19] and Hannon et al [20] in 1988. Today XRMS has become a standard tool for the study of magnetization in multilayers, magnetization reversal processes in individual layers and magnetic roughness.…”
Section: X-ray Resonant Magnetic Scatteringmentioning
confidence: 83%
“…It has been demonstrated for the first time by Gibbs et al [19] and Hannon et al [20] in 1988. Today XRMS has become a standard tool for the study of magnetization in multilayers, magnetization reversal processes in individual layers and magnetic roughness.…”
Section: X-ray Resonant Magnetic Scatteringmentioning
confidence: 83%
“…Such edges are convenient to work with, as the effects of air and sample absorption are not so severe. For example, experiments on the spiral magnetic structure of holmium at the L edges found a fiftyfold resonant enhancement of the diffraction [4,5]. At the M edge even larger effects have been observed, e.g., in uranium arsenide (UAs) an enhancement of 7 orders of magnitude was observed at the M IV edge (3.7 keV) and 5 orders of magnitude at the M V edge [6].…”
Section: P H Y S I C a L R E V I E W L E T T E R S Week Ending 9 May mentioning
confidence: 92%
“…At that time progress in studying magnetic structures using x rays was severely hampered because the cross section for magnetic scattering is smaller than the cross section for charge scattering 1 by a factor of ͑ប / mc 2 ͒ 2 . It was Gibbs et al 22 who first observed a large resonant enhancement of the cross section when the energy of the x ray is tuned through an absorption edge. Since that time technological advances have produced high resolution, high intensity synchrotron radiation sources that have transformed magnetic x-ray resonant scattering into a practical tool for investigating magnetic, and electronic structures of materials.…”
Section: Introductionmentioning
confidence: 99%